2011
DOI: 10.1007/s12206-011-0730-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on hysteresis phenomena of shock wave structure in an over-expanded axisymmetric jet

Abstract: In recent studies on two-dimensional supersonic jets, it is reported that the hysteresis phenomenon for the reflection type of shock waves in the jet flow field is occurred under the quasi-steady flow condition and this phenomenon is affected by the transitional pressure ratio between the regular reflection and Mach reflection. However, so far, there are few researches on the hysteresis phenomenon for the transition of shock waves between regular and Mach reflection in over-expanded supersonic jets and the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…As expected, this length variation is strongly related to the structure of the shock wave reflection. In the over-expanded regime, the reflected shock wave does not produce an equal deflection, and the subsequent shock occurs in a closer position than in the under-expanded case [18]. For the two different flow regimes, fig.…”
Section: Flow Visualizationmentioning
confidence: 87%
“…As expected, this length variation is strongly related to the structure of the shock wave reflection. In the over-expanded regime, the reflected shock wave does not produce an equal deflection, and the subsequent shock occurs in a closer position than in the under-expanded case [18]. For the two different flow regimes, fig.…”
Section: Flow Visualizationmentioning
confidence: 87%
“…In the over-expanded regime the reflected shock wave does not produce an equal deflection, and the subsequent shock occurs in a closer position than in the under-expanded case (Hadjadj, Kudryavtsev & Ivanov 2004; Matsuo et al. 2011). Figure 5 shows the pixel displacement trends along the jet axis () normalised with respect to its mean value in the case of over-expansion (figure 5 a ) and under-expansion (figure 5 b ), respectively.…”
Section: Flow Qualificationmentioning
confidence: 99%
“…Menon & Skews (2010) analysed the evolution of rectangular jets and other non-axisymmetric jets for various pressure ratios corresponding to the underexpanded regime and observed that the shock transition process depends on the aspect ratio and shape of the nozzle exit. Experimental and computational studies of the shock interactions in the overexpanded axisymmetric jets have been carried out by Matsuo et al (2011). They experimentally verified the presence of shock transition in the overexpanded jets for different nozzles exit Mach numbers.…”
Section: Introductionmentioning
confidence: 98%
“…Experimental and computational studies of the shock interactions in the overexpanded axisymmetric jets have been carried out by Matsuo et al. (2011). They experimentally verified the presence of shock transition in the overexpanded jets for different nozzles exit Mach numbers.…”
Section: Introductionmentioning
confidence: 99%